Epidemiology of Type 2 Diabetes Mellitus Cases in the Elderly at Gamping I Community Health Center of Yogyakarta - Dea Dwi Ramadanty (Miracle Journal of Public Health, 2022)
The increase in the elderly population is in line with the shift in the pattern of degenerative diseases. One of the degenerative diseases that has become an important problem is diabetes mellitus (DM). This study describes insulin and non-insulin Diabetes Mellitus based on epidemiological variables, namely people, place and time variables. Descriptive research design with a case series approach. The sources of patient data that we used in the form of a name, date of birth, gender, and total blood sugar levels were obtained through recording in the patient's medical record book during November 2021 at the Gamping 1 Health Center, Sleman Regency, Special Region of Yogyakarta, Indonesia. Twenty-five diabetes mellitus patients registered in the medical record during the month of November 2021 are the case in this study. All cases had type 2 DM. The distribution of patients with Diabetes Mellitus (DM) 2 was 52% male and almost the same gender as female 48%. The age of cases under 60 years was 52% and those over 60 years was 48%. The type of therapy that was obtained was a small proportion who received insulin injections, namely 24% and dominantly did not receive insulin injections or DM drugs through the brain, namely 76%. The level of GDP in cases varied widely, the highest was 415 mg/dL and the lowest was 118 mg/dL. It can be concluded that there are differences in glucose levels in each patient because each patient has a different level of pancreatic damage.